Very long baseline interferometry with the SKA - Paragi, Z.; Godfrey, L.; Reynolds, C.; Rioja, M.; Deller, A.; Zhang, B.; Gurvits, L.; Bietenholz, M.; Szomoru, A.; Bignall, H.; Boven, P.; Charlot, P.; et al. (SPIE - Internatioal Society for Optocal Engineering, 2014)
Adding VLBI capability to the SKA arrays will greatly broaden the science of the SKA, and is feasible within the current specifications. SKA-VLBI can be initially implemented by providing phased-array outputs for SKA1-MID and SKA1-SUR and using these extremely sensitive stations with other radio telescopes, and in SKA2 by realising a distributed configuration providing baselines up to thousands of km, merging it with existing VLBI networks. The motivation for and the possible realization of SKA-VLBI is described in this paper.